2015
DOI: 10.1007/s10620-015-3714-9
|View full text |Cite
|
Sign up to set email alerts
|

The Risks of Incident and Recurrent Clostridium difficile-Associated Diarrhea in Chronic Kidney Disease and End-Stage Kidney Disease Patients: A Systematic Review and Meta-Analysis

Abstract: This meta-analysis demonstrates significantly increased risks of incident and recurrent C. difficile-associated diarrhea in patients with CKD. Furthermore, the magnitude of increased risk of C. difficile-associated diarrhea in ESRD patients is even higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 38 publications
0
35
0
1
Order By: Relevance
“…In overall cohort, 20.3% of the patients experienced initial metronidazole treatment failure, but the failure rate in CKD patients was 16.7%, which was not higher than that in control patients. The clinical features of complicated CDI, such as ileus or toxic megacolon in CKD patients, were also not more frequent than in non-CKD patients, and the incidence of recurrent CDI was not significantly different among groups unlike the previous findings [30,31]. Nevertheless, when compared with CDI patients without CKD, initial metronidazole therapy in those undergoing dialysis tended to be associated with an increased risk of treatment failure.…”
Section: Discussionmentioning
confidence: 57%
“…In overall cohort, 20.3% of the patients experienced initial metronidazole treatment failure, but the failure rate in CKD patients was 16.7%, which was not higher than that in control patients. The clinical features of complicated CDI, such as ileus or toxic megacolon in CKD patients, were also not more frequent than in non-CKD patients, and the incidence of recurrent CDI was not significantly different among groups unlike the previous findings [30,31]. Nevertheless, when compared with CDI patients without CKD, initial metronidazole therapy in those undergoing dialysis tended to be associated with an increased risk of treatment failure.…”
Section: Discussionmentioning
confidence: 57%
“…A meta-analysis of 20 clinical studies (observational, cohort and case control) including 162 million individuals showed significantly higher risk of CDI and CDI recurrence in patients with chronic kidney disease (1.95-fold and 2.61-fold increased risks, respectively). Moreover, in ten studies, a significantly increased CDI risk was demonstrated in patients with end-stage renal disease (2.63-fold increased risk) [31]. Similarly, a meta-analysis of 19 studies (case-control and 18 cohort studies) showed that patient with CKD have an increased risk of severe or recurrent CDI, and increased CDI mortality risk (1.51-fold, 2.73-fold and 1.76-fold increased risks, respectively) [32].…”
Section: Clostridium Difficile Infection In Patients Hospitalized In mentioning
confidence: 99%
“…Increased risk of CDI in patients with CKD can be caused by: frequent antibiotic therapy associated with numerous infections resulting in intestinal microflora dysfunction, frequent hospitalizations, older age of the patients and an impaired immune system [31]. …”
Section: Clostridium Difficile Infection In Patients Hospitalized In mentioning
confidence: 99%
“…Adverse events as a result of antimicrobial exposure include drug-drug interactions, Clostridium difficile infections, allergic reactions and drug fever. The latter can lead to significant additional work-up and potentially more antimicrobial exposure [18,19]. Thus, ASP should provide guidelines and implement strategies to reduce the antimicrobial therapy to its shortest effective duration.…”
Section: Introductionmentioning
confidence: 99%
“…Other outcomes that can be measured include adverse events related to antimicrobials, such as C. difficile infections and rates of antimicrobial susceptibility over time [18,19]. Although many institutions also track improved costs associated with the ASP, this outcome only takes into account costs associated with decreasing antimicrobial use and does not take into consideration the tremendous cost savings of preventing the emergence of antimicrobial resistance or the economic burden associated with C. difficile infections and hospitalizations.…”
Section: Introductionmentioning
confidence: 99%